Determinants of Technical Efficiency in Agricultural Production among Sub Saharan African Countries - Ntwiga, Davis Bundi (Journal of Agriculture and Environmental Sciences, 2021)
Climate change has led to a decline in agricultural production due to erratic weather patterns, compromised crop yields and population pressure on arable land. Sub-Saharan Africa is most vulnerable to climate change due to its geographical location, increase in population, destruction of the forests and other agricultural malpractices. This is a threat to livelihoods, food systems, and increase in malnutrition and shocks in food prices. This study examines the influence of climatic factors on the technical efficiency of agricultural production in Sub Saharan Africa using time series data for 25 years from 1991 to 2015 selected from nine countries. The data envelopment analysis estimates technical efficiency with input variable as agricultural land and output variable as agricultural value-added. The panel data analysis response variable is the technical efficiency scores. Predictor variables were population, forest area, temperature, rainfall, and greenhouse gases. In the last 25 years, there has been an increase in population, agricultural land, temperature, and greenhouse gases with a decrease in forest area and rainfall. Temperature, forest area, and greenhouse gases showed significant influences on the technical efficiency of agricultural production. The intricate nature of climate change requires significant efforts to reverse the trend being observed and boost agricultural production efficiency.